The Role of Academic Supervision Management with a Coaching Mindset in Developing Elementary School Teachers’ Pedagogical Competence: Evidence from Two Schools in Sukabumi - Saripah, Eneng; Suwandari, Lilis (Journal of Innovation and Research in Primary Education, 2025)
This study investigates the management of academic supervision with a coaching mindset to enhance the pedagogical competence of elementary school teachers. Recognizing the limitations of traditional evaluative supervision, the research explores coaching-based approaches that emphasize reflection, collaboration, and empowerment. Employing a qualitative descriptive design, data were collected through interviews, observations, and documentation from two elementary schools representing public and private contexts. The findings reveal that while coaching principles—such as reflective dialogue, collaborative goal-setting, and empowerment-focused feedback—have been partially implemented, their application remains inconsistent across supervisory practices. Teachers reported increased motivation and professional growth, yet challenges persist in supervisor competencies, differentiated coaching strategies, and documentation systems. The study concludes that coaching-oriented supervision offers a transformative model for teacher development, contingent upon leadership capacity and institutional readiness. Practical implications include the need for targeted training for school leaders and the development of structured supervision frameworks that support reflective practice and continuous improvement.